2012
DOI: 10.33225/pec/12.49.15
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ict to Raise Students’ Achievement in Italian Technical and Professional Schools

Abstract: The research examines the role of using ICT to raise students’ achievement in Italian technical and professional schools. The hypothesis developed in this research is that students who obtain better learning results are those students who use ICT more than those students who are low performers. Data from the Programme for International Student Assessment (PISA) 2009 by OECD (Organisation for Economic Co-operation and Development) have been analyzed. The relationship between using ICT at school and students’ di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The influence of ICT on student achievement is still a matter of debate in most large-scale international studies conducted by researchers using different variables and methodologies (Erdogdu and Erdogdu, 2015; Petko et al, 2017). Some of these studies reported findings on the positive effects of ICT use on academic achievements (Aşkar and Olkun, 2005; Delen and Bulut 2011; Erdogdu and Erdogdu, 2015; Freddano and Diana, 2012; Kubiatko and Vlckova, 2010; Leino, 2014; Zhang and Liu, 2016). For example, Zhang and Liu (2016), in their study using PISA data from 2000 to 2012, found that when Gross National Product (GNP), school type and school ICT investments were controlled, the variables related to ICT at school-level had positive influence on learning outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of ICT on student achievement is still a matter of debate in most large-scale international studies conducted by researchers using different variables and methodologies (Erdogdu and Erdogdu, 2015; Petko et al, 2017). Some of these studies reported findings on the positive effects of ICT use on academic achievements (Aşkar and Olkun, 2005; Delen and Bulut 2011; Erdogdu and Erdogdu, 2015; Freddano and Diana, 2012; Kubiatko and Vlckova, 2010; Leino, 2014; Zhang and Liu, 2016). For example, Zhang and Liu (2016), in their study using PISA data from 2000 to 2012, found that when Gross National Product (GNP), school type and school ICT investments were controlled, the variables related to ICT at school-level had positive influence on learning outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, in one study with Finnish students, Leino (2014) showed that surfing on the Internet increases reading skills depending on the person’s familiarity with searching data on the Internet. In another study, according to PISA 2009, the Italian students with high levels of success in reading used the computer better than those with low levels of success in reading and that ICT had a more positive effect on the students’ success (Freddano and Diana, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%